2015
DOI: 10.1016/j.neunet.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A GPU-accelerated cortical neural network model for visually guided robot navigation

Abstract: Humans and other terrestrial animals use vision to traverse novel cluttered environments with apparent ease. On one hand, although much is known about the behavioral dynamics of steering in humans, it remains unclear how relevant perceptual variables might be represented in the brain. On the other hand, although a wealth of data exists about the neural circuitry that is concerned with the perception of self-motion variables such as the current direction of travel, little research has been devoted to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In the first experiment, (n 4 , τ 4 ) is set as (1,5), (2,10), (3,15), (4,20), (5,25), (6,30). In the second experiment, (n 5 , τ 5 ) is set as (3,15), (4,20), (5,25), (6,30), (7,35), (8,40). In the third experiment, (σ 4 , σ 5 ) is set as (1.0, 2.0), (1.5, 3.0), (2.3, 4.6), (2.8, 5.6), (3.7, 7.4).…”
Section: Parameter Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the first experiment, (n 4 , τ 4 ) is set as (1,5), (2,10), (3,15), (4,20), (5,25), (6,30). In the second experiment, (n 5 , τ 5 ) is set as (3,15), (4,20), (5,25), (6,30), (7,35), (8,40). In the third experiment, (σ 4 , σ 5 ) is set as (1.0, 2.0), (1.5, 3.0), (2.3, 4.6), (2.8, 5.6), (3.7, 7.4).…”
Section: Parameter Sensitivitymentioning
confidence: 99%
“…Tuning properties of the proposed neural network under different parameter (n 5 , τ 5 ). In this experiment, (n 5 , τ 5 ) is set as(3,15),(4,20),(5,25),(6,30),(7,35),(8,40) while the other parameters are fixed. In each subplot, the horizontal axis represents one of the target parameters (Weber Contrast, velocity, width, and height) while the vertical axis denotes normalized model outputs.…”
mentioning
confidence: 99%
“…Taking the neural network as the starting point, the nonlinear system identification method based on neural network and the network characteristics commonly used for identification are discussed. Study showed the neural network is optimized from two aspects of network topology and learning algorithm [4]. The neural network identification model of multi-layer forward neural network and dynamic regression neural network based on improved Elman algorithm is studied.…”
Section: Introductionmentioning
confidence: 99%
“…DNA- 28 based analyses have been applied to the field of forensic entomology for over a decade [6]. They 29 have been successfully used to identify and age forensically important species [7][8][9][10][11]. 30 One technique that may have the potential to give the same accuracy as DNA-based techniques for 31 an ageing tool is Cuticular Hydrocarbon (CHC) analysis [12].…”
mentioning
confidence: 99%
“…and have the ability to learn the relationship between input and output data, making them well-55 suited to fast processing of large real-world datasets (e.g. speech recognition [28], robotics [29], 56 structural engineering [30] as well as the forensic sciences [31].…”
mentioning
confidence: 99%